Stress‐related biomarkers in dogs administered regional anaesthesia or fentanyl for analgesia during stifle surgery. (20th May 2015) - Romano, Marta; Portela, Diego A; Breghi, Gloria; Otero, Pablo E
Abstract: Objectives: To compare the effects of regional anaesthesia and opioid administration on adrenocortical and glycaemic responses, postoperative pain and recovery quality in dogs undergoing stifle surgery. Study design: Prospective, blinded clinical study. Animals: Forty‐five dogs anaesthetized for tibial tuberosity advancement or tibial plateau levelling osteotomy, and 15 healthy dogs undergoing non‐invasive orthopaedic diagnostic procedures. Methods: The baseline behaviour of each dog was classified on a descriptive scale before anaesthesia. Dogs were anaesthetized using a standard protocol. Those undergoing surgery were randomly assigned to one of three intraoperative analgesia protocols: 1) peripheral (femoral and sciatic) nerve block (bupivacaine 0.5%; 0.15 mL kg −1 in each nerve; group PNB); 2) spinal anaesthesia (isobaric bupivacaine 0.5%; 0.05 mL kg −1 ; group SPI); and 3) intravenous fentanyl variable rate infusion and postoperative methadone (0.2 mg kg −1 ; group FEN). Blood samples were collected for measurement of cortisol and glucose concentrations on arrival (TAR ), at induction (TIND ), at tracheal extubation (TEXT ), and 1 hour post‐extubation (TPEX ). After extubation, a researcher unaware of the dog's group assignment evaluated pain and recovery quality using the Glasgow Composite Measure Pain Scale (Short‐Form) and a descriptive scale, respectively. Results: Median recovery quality was significantly worse in group FEN ( p  < 0.0001) compared with all other groups. Postoperative pain scores were lower in group PNB compared with groups SPI and FEN. Cortisol and glucose concentrations increased significantly from TAR at TEXT and TPEX ( p  < 0.0001) in group FEN, and were unchanged from TAR in the other groups. Conclusions and clinical relevance: Analgesia with a peripheral nerve block or spinal anaesthesia prevented the glycaemic and cortisol responses to surgery, promoted better recovery quality, and decreased postoperative pain scores compared with FEN. In the present study, the regional anaesthesia techniques used were found to be excellent alternatives to fentanyl administration.